Pterygium as a Potential Ocular Manifestation of Morphea: A Case Report and Pathogenic Hypothesis - Woźna, Julia; Pazdrowski, Paweł; Helak-Łapaj, Celina; Markwitz, Maksymilian; Polańska, Adriana; Stopa, Marcin; Dańczak-Pazdrowska, Aleksandra (Dermatology Review/Przegląd Dermatologiczny, 2025)
Morphea, or localized scleroderma, is a chronic inflammatory condition marked by excessive collagen deposition, resulting in skin thickening and fibrosis. We report the rare case of a 54-year-old woman with en coup de sabre morphea overlapping with progressive facial hemiatrophy, who additionally presented with a pterygium. Systemic immunosuppressive therapy was initiated due to disease progression. The case underscores the importance of multidisciplinary assessment in atypical morphea presentations and raises the question of a potential association between fibrotic ocular pathology such as pterygium and underlying autoimmune connective tissue disease. Recent findings suggest overactivation of the p53 pathway in both morphea and pterygium, potentially linking their fibrotic mechanisms. Further research is warranted to explore this intersection.